Kawaii i hallyu – wykorzystanie kultury popularnej w charakterze soft power Japonii i Korei Południowej - Marek SOKOŁOWSKI (Przegląd Geopolityczny)
The article draws attention to important elements of contemporary popular culture of two Far Easter countries – Japan and South Korea. Japan has the original kawaii culture; South Korea has the hallyu culture. Over recent years, products of both Japanese and Korean popular culture have been massively exported and consumed throughout East and Southeast Asia. The expansion of cute kawaii creativity in the form of Japanese animated films, comics, including Hello Kitty and Pokemon characters allowed this culture to appear in the USA and Europe (also in Poland), causing an international phenomenon called “pink globalization”. The “Korean Wave” (hallyu), based mainly on the expansion of pop music and television dramas, attracted similar interest. The aim of the article is to analyze, using a qualitative research paradigm, the importance of kawaii and hallyu culture in building the international position of Japan and South Korea, perceived today as local civil powers. Both the Japanese and Korean governments use popular culture in their cultural diplomacy as soft power, as defined by American political scientist Joseph S. Nye. The researcher concluded that soft power, unlike hard power, is the power of attraction, “seduction”, which consists in the attractiveness of the culture of the entity controlling the preferences of others.